Os desafios dos profissionais de segurança pública e suas relações com o bem-estar social e o bem-estar social no trabalho - Corrêa, Jonathan Saidelles (2022)
Professionals in the area of public security live daily with a plurality of feelings, since they carry out their activities in the midst of high levels of tension. In this field, they are included as Military, Civil and Criminal Police, whose work environment can reveal daily challenges capable of negatively influencing the health of individuals. Their duties often spill over into their personal lives, given that police officers, for example, have professional obligations even when they are not on duty. In this sense, it is important to understand how these challenges affect the health of professionals. According to the World Health Organization, health is a state of complete physical, mental and social wellbeing. As a result, this research seeks to analyze the relationships between the types of challenges faced by public security professionals and the components of Social Wellbeing and Social Wellbeing at Work. In order to do so, it was necessary to build the Public Safety Professionals Challenge Scale, as well as carry out the cross-cultural adaptation and validation of the Social Well-being Scales (SWBS), developed by Keyes (1998), as well as the Occupational Social Wellbeing Inventory. (OSWI), which was developed by Ali Kazemi (2017). Keyes (1998) defines Social Wellbeing as a set of challenges that each individual faces in their social life, encompassing aspects of integration, acceptance and even contribution to the community and/or society in which they are inserted. In turn, Occupational Social Wellbeing means social life properly experienced in the context of work (KAZEMI, 2017). For that, an exploratory and descriptive research was used, of the survey type, using qualitative and quantitative approaches. The sample consisted of 1292 public security professionals in Brazil. Data analysis took place through Structural Equation Modeling. The results demonstrated the statistical adequacy of the constructed scale, as well as the two foreign scales adapted for Brazil. The hypotheses confirmed that the Health Challenges caused by the public security profession tend to have a negative impact on all dimensions of Social Wellbeing and Social Wellbeing at Work. In turn, the results confirmed that Social Challenges tend to have a negative influence only on the professional's integration with society, on the professional's trust in other citizens and on the future perspective of society. Still, the study showed that Social Challenges can increase integration and companionship among co-workers, although this relationship has not been confirmed with colleagues who have leadership positions. The conclusions demonstrate the need for continuous assessment of security professionals regarding these issues and also reinforced the importance of psychological treatment to prevent illness due to trauma linked to the performance of the profession. As suggestions for future studies, it highlights the deepening of statistical analyzes that allow improving the discriminant validity and the face validity of scales. It would also be relevant to apply the scales in stratified samples, aiming to verify the statistical adequacy for more homogeneous samples, which have, for example, a symmetrical control of the number of police officers from different careers, as well as from different genres, professional activities and regions of the country.